Mitigation of Waste Pollution in Coastal Ecosystems and Mangrove Forests in Coastal Areas - Lasaiba, Mohammad Amin; Rifai, Ahmad; Muin, Abdul (Jurnal Pengabdian Arumbai, 2024)
The preservation of coastal ecosystems and mangrove forests is becoming increasingly urgent due to their vital role in maintaining the overall balance of ecosystems. The presence of mangrove forests can reduce the impact of coastal erosion and protect from threatening sea storms. Furthermore, mangrove ecosystems serve as habitats for various species. This community service program utilizes a participatory and educational approach to address plastic pollution on the coast of Batu Koneng Beach, Poka Village, Ambon Island, Maluku. The GEMPA Nature Lovers, students from the Geography Education Study Program at Pattimura University in Ambon, collaborated with the Indonesian Sea Guardians Community, the 733/Raider Infantry Battalion, and local communities. The program's goal is to raise awareness among the community and create a tangible impact in maintaining coastal environmental cleanliness. The chosen location has a significant plastic pollution issue, offering great potential for environmental preservation activities. The GEMPA Nature Lovers, a student organization passionate about the environment, constitute the program's primary participants. The program's main findings underscore the importance of awareness and tangible actions in addressing plastic pollution on the coast. By involving students, local communities, and various stakeholders, the program enhances understanding of the negative impacts of plastic pollution and the importance of preserving coastal ecosystems. These findings provide a strong foundation for developing sustainable policies and practices in waste management and protecting coastal ecosystems.